Kontribusi Kepercayaan Diri Terhadap Keberhasilan Teknik Headstand Dalam Senam Lantai Pada Mahasiswi Pendidikan Olahraga Angkatan 2022 Universitas Riau - Ayu, Melina Pabila Rina; Ardiah Juita; Muhammad Imam Rahmatullah; Siti Maesaroh; Balqis Amirah Adli (Universitas Singaperbangsa Karawang, 2023)
Every research activity certainly has aims and objectives. Based on the existing problem formulation, this study aims to determine the contribution of self-confidence to the success of the techniqueheadstand floor exercise for physical education students at the University of Riau class of 2022. The research was conducted from November to December 2022 with female students of the Faculty of Physical Education, Teacher Training and Education, University of Riau, class of 2022. The sampling technique was purposive sampling with a total of 55 female students and the data collection technique was carried out through questionnaires and practice tests headstand. From the results of the research process to data processing which began with data collection to conduct trials of research instruments as many as 30 Riau University students stated that there were 24 valid statement items processed using IBM SPSS Statistics 24. Research with a quantitative correlation approach with the aim to see the contribution of self-confidence to technique successheadstand. Where the results of the study did not contribute to the success of the technique headstand in floor exercises for students of sports education class of 2022 at the University of Riau, it is known from the results of the simple correlation test sig(2-tailed) it has a result of 0.532> sig(2-tailed) 0.05 and where Rcount is -0.86<Rtable 0.266 and enters in the category of 0.00-0.199